Let f(x)= 1/(x^2 -4)

We need to determine F(x) such that:

F(x) = intg f(x) dx

==>F(x) = intg [ 1/(x^2 - 4)] dx

Let us simplify:

1/(x^2 -4) = 1/(x-2)(x+2)

==> = A/(x-2) + B/(x+2)

==> A(x+2) + B(x-2) = 1

Open brackets:

==> Ax 2A + Bx - 2B = 1

==> (A+B) x + 2(A-b) = 1

==> A+b = 0 .....(1)

==> A-b = 1/2......(2)

Now add (1) and (2):

==> 2A = 1/2

==>** A = 1/4**

**==> B = -1/4**

==> 1/(x^2 - 4) = 1/4(x-2) - 1/4(x+2)

==> F(x) = intg [1/4(x-2) - 1/4(x+2) ] dx

= (1/4)*( intg 1/(x-2) dx - intg 1/(x+2) dx

= (1/4)* [ ln (x-2) - ln (x+2) ] + C

= (1/4) ln (x-2)/(x+2) + C

**==> F(x) = (1/4)*ln (x-2)/(x+2) + C **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now